2013
DOI: 10.3389/fphys.2013.00398
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HSP25 loss on muscle contractile function and running wheel activity in young and old mice

Abstract: Aging is associated with an adverse decline in muscle function, often manifesting as decreased strength and increased muscle fatigability that negatively affects the overall health of the elderly. Heat shock proteins (HSPs), a family of stress inducible proteins known to protect cells from damage, are highly induced in muscle cells following exercise, but both basal and inducible levels decline with age. Utilizing young and old mice lacking HSP25 (Hsp25−/−) we tested the hypothesis that HSP25 is required to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
0
11
1
Order By: Relevance
“…Exercise promotes the HSP70 response (Milne & Noble, 2002;Salo et al, 1991), and this effect is also in agreement with the results of the present study because, independently of the peptide consumed, exercise caused HSP70 upregulation. HSP25 is detectable in unstressed tissue and may elevate its expression as a result of environmental perturbations (Gernold et al, 1993), including exercise (Huey & Meador, 2008;Huey et al, 2013). Our data showed that exercise elevated only the HSP25 expression in the groups that received Leu-Val, whereas the HSP25 expression in the groups that received the other peptides did not differ from that of the control (rest).…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…Exercise promotes the HSP70 response (Milne & Noble, 2002;Salo et al, 1991), and this effect is also in agreement with the results of the present study because, independently of the peptide consumed, exercise caused HSP70 upregulation. HSP25 is detectable in unstressed tissue and may elevate its expression as a result of environmental perturbations (Gernold et al, 1993), including exercise (Huey & Meador, 2008;Huey et al, 2013). Our data showed that exercise elevated only the HSP25 expression in the groups that received Leu-Val, whereas the HSP25 expression in the groups that received the other peptides did not differ from that of the control (rest).…”
Section: Discussioncontrasting
confidence: 73%
“…Similarly, the predominant accumulation of HSP25 in muscle tissue is involved in the organization of the intracellular matrix, the preservation of cell structure, stress resistance (Gernold, Knauf, Gaestel, Stahl, & Kloetzel, 1993), the prevention of and protection against oxidative and thermal damage (Musch, Kapil, & Chang, 2004) and the repair of muscle damage (Huey et al, 2013). Mice lacking HSP25 (Hsp25 −/−) run shorter distances, have reduced myofibrillar (contractile) protein levels and develop fatigue more rapidly than the Hsp25+/+ mice, suggesting that HSP25 expression is required to maintain adequate muscle function (Huey et al, 2013). The HSP70 and HSP25 responses both promote stress resistance (Gernold et al, 1993), protect tissues during exercise (Huey & Meador, 2008), and alter homeostasis (Nishizawa et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…g . increased physical activity [ 10 ] [ 11 ] including lifelong training [ 12 ], endurance training [ 13 ], and eccentric exercise [ 14 ]. Some protective functions of Hsp27 are suggested by its translocation from the cytosolic to myofibrillar fraction and binding to cytoskeletal structures such as Z-disk proteins [ 15 ] [ 14 ].…”
Section: Introductionmentioning
confidence: 99%